The impact of childhood exposure to destructive forms of inter-parental conflict and of separation/divorce - Jones, Richard T. (2018)
Background: Existing theories and research are provided, detailing the harmful effects of childhood exposure to destructive forms of inter-parental conflict. This area of research is lacking in comparison to that of adult perpetrators and victims of domestic violence. Equally, there is a general emphasis towards inter-parental violence instead of other forms of inter-parental conflict.